2016
DOI: 10.4236/ojog.2016.610076
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Early Discontinuation of Breastfeeding in Iranian Mothers

Abstract: Objective: The present study was conducted to evaluate the risk factors that reduce the rate of breastfeeding among Iranian women in the first six months after delivery. Materials and Methods: This cross sectional study was performed on 542 mothers with infants less than six months old who came to Taleghani Hospital, Tehran, Iran, for vaccination follow up, from 2012 to 2014. Trained examiners filled a predesigned questionnaire including information about breastfeeding and factors that may affect the mode of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…The results revealed that breast feeding was predominant in non-pacifier sucking group (70%) than pacifier sucking group (8%), Table (3), this finding is in accordance with other studies (18,19) , children will less likely to have been exclusively breastfed if they use of pacifier early in infancy.…”
Section: Discussionsupporting
confidence: 90%
“…The results revealed that breast feeding was predominant in non-pacifier sucking group (70%) than pacifier sucking group (8%), Table (3), this finding is in accordance with other studies (18,19) , children will less likely to have been exclusively breastfed if they use of pacifier early in infancy.…”
Section: Discussionsupporting
confidence: 90%